Salvage Surgery in Recurrent Oral Squamous Cell Carcinoma - K. S. Rathan Shetty; Vinayak Kurle; P. Greeshma; Veena B. Ganga; Samskruthi P. Murthy; Siddappa K. Thammaiah; P. Krishna Prasad; Purushottham Chavan; Rajshekar Halkud; R. Krishnappa (Frontiers Media S.A., 2022)
More than half of patients with oral cancer recur even after multimodality treatment and recurrent oral cancers carry a poorer prognosis when compared to other sites of head and neck. The best survival outcome in a recurrent setting is achieved by salvage surgery; however, objective criteria to select an ideal candidate for salvage surgery is difficult to frame, as the outcome depends on various treatment-, tumor-, and patient-related factors. The following is summarizes various tumor- and treatment-related factors that guide our decision-making to optimize oncologic and functional outcomes in surgical salvage for recurrent oral cancers. Short disease-free interval, advanced tumor stage (recurrent and primary), extracapsular spread and positive tumor margins in a recurrent tumor, regional recurrence, and multimodality treatment of primary tumor all portend worse outcomes after surgical salvage. Quality of life after surgical intervention has shown improvement over 1 year with a drastic drop in pain scores. Various trials are underway evaluating the combination of immunotherapy and surgical salvage in recurrent head and neck tumors, including oral cavity, which may widen our indications for salvage surgery with improved survival and preserved organ function.